Puerperal choriocarcinoma. (2nd February 2011) - Beavington, L; Mossa, M
Abstract : A 32-year-old lady presented postnatally with headaches, blurred vision and left leg numbness, which was initially diagnosed as migraine with sciatica. Subsequently, she developed seizures and was admitted to ITU. Investigations revealed abnormal grey matter perfusion in the right occipital region of the brain, multiple lung nodules, lesions in the liver and a pancreatic mass. A β-human chorionic gonadotrophin level was over 132 000 IU/l, and metastatic choriocarcinoma was diagnosed. She responded well to combination chemotherapy and made a full recovery.